Identification of loci associated with schizophrenia by genome-wide association and follow-up - O'Donovan, Michael C; Craddock, Nicholas; Norton, Nadine; Williams, Hywel; Peirce, Timothy; Moskvina, Valentina; Nikolov, Ivan; Hamshere, Marian; Carroll, Liam; Georgieva, Lyudmila; Dwyer, Sarah; Holmans, Peter; et al. (Nature genetics, 2008)
Michael O'Donovan and colleagues present a genome-wide association study of schizophrenia in 479 cases and 2,937 controls, followed by replication in several cohorts. They report evidence for association for a susceptibility allele near ZNF804A . We carried out a genome-wide association study of schizophrenia (479 cases, 2,937 controls) and tested loci with P < 10 −5 in up to 16,726 additional subjects. Of 12 loci followed up, 3 had strong independent support ( P < 5 × 10 −4 ), and the overall pattern of replication was unlikely to occur by chance ( P = 9 × 10 −8 ). Meta-analysis provided strongest evidence for association around ZNF804A ( P = 1.61 × 10 −7 ) and this strengthened when the affected phenotype included bipolar disorder ( P = 9.96 × 10 −9 ).